Glycome dynamics in T and B cell development: basic immunological mechanisms and clinical applications - Vicente, MM (2023)
Glycans cover the surfaces of all mammalian cells through a process called glycosylation. Nearly all proteins and receptors that integrate the intricate series of co-stimulatory/inhibitory pathways of the immune system are glycosylated. Growing evidence indicates that the development of the immune system at the origins of T and B cell development is tightly regulated by glycosylation. In this opinion, we hypothesize that the glycome composition of developing T and B cells is developmentally regulated. We discuss how glycans play fundamental roles in lymphocyte development and how glycans early define T and B cell functionality in multiple aspects of adaptive immunity. These advances can provide opportunities for the discovery of novel disease factors and more effective candidate treatments for various conditions.